Implementasi Pembelajaran Pendidikan Agama Islam Dalam Pelajaran Akidah Akhlak Untuk Membentuk Karakter Islami Siswa Kelas II - Aris Salman Alfarezi (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
The background of this research is that character building is an effort that involves all parties, including parents, schools, the school environment, and the wider community. The combination, harmony, and continuity of the parties contribute directly to the formation of a person's character. In other words, without the involvement of the parties, character education will be limping, slow and weak and even threatened with failure. In general, the parties want students to be competent in their fields and have character. Therefore, the parties must work together and take their respective roles in an effort to build the character of students. The type of research used in this study is qualitative research. The research used is descriptive qualitative research. Descriptive qualitative research is a form of research with a case study method or approach (cash study). This research focuses intensively on a particular object that studies as a case. Case study data can be obtained from all parties concerned, in other words, in this study collected in various sources to provide solutions on how to form Islamic character in MI darul Akhyar. The results of the research based on the analysis and discussion found that the implementation of Islamic character education in selokah includes by doing habituation such as Dhuha prayers, congregational dhuhur prayers, reading the Qur'an or reading iqro and memorising short letters contained in the Qur'an. In addition, students before starting learning are always given advice containing religious matters, for example such as adab or ahklak so that students can respect teachers or teaching staff where they study.